STRATEGI KEYWORD METHOD UNTUK MENINGKATKAN PENGUASAAN KOSAKATA - Kurniawan, Ryan; Sugiyadi, Sugiyadi; Rasidi, Rasidi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2013)
This study aims to improve students? vocabulary mastery of grade IV SDN Kemirirejo 3 Magelang through strategic keyword method. This type of research is the Classroom Action Research. The subjects were teachers and students of Elementary School fourth grade totaling Kemirirejo 3 31siswa. This study uses a vocabulary test data collecting and using data analysis techniques such as qualitative descriptions. Criteria for success of the action in the research are the success criteria seen from the development process of vocabularylearning process. Product success criteria based on student success in improving vocabulary reflecting their understanding of vocabulary. The validity of the data in this study include the validity of democracy which researchers actually collaborate with peers, teachers, and students and receive input from various parties to strive to increase the vocabulary in the learning process, the validity of dialogue that the research was conducted by means of dialogue with peers and collaborator to seek criticism and constructive suggestions.The results showed an increase in vocabulary can be seen from the increasing number of students who value belonging to the category of qualified and not qualified . In the first cycle of students who graduated reached 14 children from a total of 31 children , then the second cycle students who graduated reached 29 children . With the passing rate in the first cycle is 45.16 % with an average grade 66.97 and the second cycle increased to 93.55 % with an average grade 76.13 . Scores of efficiency inthe first cycle and the second cycle is 54.84 which is 0.06 . Thus, the overall value of students? skills in vocabulary in the first cycle and the second cycle increased. It can be concluded that the learning strategy can improve the Keyword Method pengguasaan vocabulary Elementary School fourth grade students Kemirirejo 3.